Penguatan Akhlak Disiplin Peserta Didik Melalui Sosialisasi Tertib Berlalu Lintas di SMK Ma’arif 1 Kebumen - Khanifiiyah, Lulu Lestari; Astuti, Astuti; Saputri, Elika; Nachroy, Faiq Ali; Khanifiiyah, Lulu Lestari Nurul; Fatimah, Siti; Chamidi, Agus Salim; Subkhan, Subkhan; Aminah, Kun (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This research was conducted at SMK Ma'arif 1 Kebumen, a school located in Bumirejo Village, sub-district. Kebumen, district. Kebumen. Most of the students at SMK Ma'arif 1 Kebumen use motorized vehicles. The condition of the traffic road to SMK Ma'arif 1 Kebumen has a high traffic volume because the school is located in the center of Kebumen city which creates a risk of accidents for students who use it. motor vehicles to school increased'. Therefore, PLP IAINU Kebumen at SMK Ma'arif 1 Kebumen held a socialization on "Strengthening the Disciplined Character of Students through Orderly Traffic" as a solution to existing problems. This form of activity aims to provide an understanding of safe and orderly driving behavior in traffic by providing material presentations and question and answer sessions related to safe and orderly driving behavior in traffic. The method used is a qualitative method with interviews, observation and documentation. The process carried out is SWOT analysis, preparation of plans and programs, consultation on plans and programs, action for implementing priority programs and evaluation and follow-up plans. The results obtained are increasing students' awareness and understanding of the importance of orderly traffic. The high enthusiasm of the participants shows that this activity is very useful and relevant to the needs of students